PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN INFORMATIKA DI SMAN 1 RANAH PESISIR - Dona Zetriani Lolita; Fetri Yeni J; Darmansyah; Novrianti (STKIP Subang, 2025)
The background of this research is that teacher-centered learning still relies on lecture and practical methods, conducted exclusively in the classroom and without laboratory facilities. This results in students becoming bored and tired during the learning process. This study aims to explore the impact of the use of audio-visual media on the learning achievement of 10th-grade students in Informatics at SMAN 1 Ranah Pesisir. This study employed a quantitative method with a quasi-experimental design, involving two sample groups: the experimental group and the control group. The sample consisted of 50 students, consisting of 25 in the control group (X1) and 25 in the experimental group (X2). The experimental group received audio-visual media, while the control group implemented traditional methods using textbooks and a whiteboard. The measurement instrument in this study was a learning test consisting of 20 multiple-choice questions that had been tested for validity (15 questions were declared valid) and reliability (r = 0.769, high category). Based on the research results, the average score of the experimental class was 75.72 with a standard deviation of 10.64, while the average score of the control class was 62.44 with a standard deviation of 10.46. The normality test using Liliefors showed that the calculated L value exceeded the t-table (α = 0.05), thus H_0 was rejected and H_1 was accepted. It can be concluded that the use of audio-visual media has a positive and significant impact on student learning achievement in Informatics.